Impact assessment of different water management technologies on regional groundwater ecosystem service - Kumar, Manoj; Singh, D. K.; Sarangi, A.; Mani, Indra; Khanna, Manoj (Frontiers in Water, 2025)
Declining groundwater table is a big sustainability challenge at Rasoolpur Jatan village of Shahpur block in Western U.P, India. This study was conducted in farmer’s fields to assess the impact of different water management technologies on water table fluctuations, aiming to develop a sustainable strategy for groundwater utilization. To simulate the future groundwater table behaviour, modeling was done. Sugarcane is a high water-demanding crop, and the maximum part of study area is under sugarcane crop, and irrigation is being done through earthen field channels. When irrigation is applied through earthen field channel with measured Application Efficiency (Ea) of 60% (baseline), the water table would decline by 0.59 meters per year (m/yr.) with respect to 2015 pre-monsoon water table of 223.31 m. When seepage loss (6%) in earthen field channel was saved (scenario 2), the water table decline would reduce to 0.46 m/yr. Laser land leveler was used and save 17% water (scenario 3), in this case water table would decline by 0.10 m/yr. If 50% sugarcane area replaced with Kharif maize (scenario 4), then water table would rise by 0.54 m/yr. Groundwater savings under scenario 2, 3, and 4 are calculated as 24.54 ha-m, 69.53 ha-m, and 159.56 ha-m, respectively, compared to the baseline. The projected groundwater table for the year 2030 under four scenarios are 213.84, 215.96, 221.67 and 232.05 m, respectively. Results suggested that to maintain the groundwater sustainability change the cropping pattern to avoid excess use of groundwater, grow other high value crops with the help of modern irrigation system which have low water demand.